Is the effect of tinnitus on auditory steady-state response amplitude mediated by attention? - Diesch, Eugen; Andermann, Martin; Rupp, André (Frontiers in Systems Neuroscience, 2012)
Objectives: The amplitude of the auditory steady-state response (ASSR) is enhanced in tinnitus. As ASSR ampli¬tude is also enhanced by attention, the effect of tinnitus on ASSR amplitude could be interpreted as an effect of attention mediated by tinnitus. As attention effects on the N1 are signi¬fi¬cantly larger than those on the ASSR, if the effect of tinnitus on ASSR amplitude were due to attention, there should be similar amplitude enhancement effects in tinnitus for the N1 component of the auditory evoked response. Methods: MEG recordings of auditory evoked responses which were previously examined for the ASSR (Diesch et al. 2010) were analysed with respect to the N1m component. Like the ASSR previously, the N1m was analysed in the source domain (source space projection). Stimuli were amplitude-modulated tones with one of three carrier fre¬quen¬cies matching the tinnitus frequency or a surrogate frequency 1½ octaves above the audio¬metric edge frequency in con¬trols, the audiometric edge frequency, and a frequency below the audio¬metric edge Results: In the earlier ASSR study (Diesch et al., 2010), the ASSR amplitude in tinnitus patients, but not in controls, was significantly larger in the (surrogate) tinnitus condition than in the edge condition. In the present study, both tinnitus patients and healthy controls show an N1m-amplitude profile identical to the one of ASSR amplitudes in healthy controls. N1m amplitudes elicited by tonal frequencies located at the audiometric edge and at the (surrogate) tinnitus frequency are smaller than N1m amplitudes elicited by sub-edge tones and do not differ among each other. Conclusions: There is no N1-amplitude enhancement effect in tinnitus. The enhancement effect of tinnitus on ASSR amplitude cannot be accounted for in terms of attention induced by tinnitus.